The theater in Hegel: reflexivity, understanding and historicity - Werle, Marco Aurelio (Estudios de Filosofía, 2012)
This article examines the Hegelian idea of modern art in the light of considerations about the theatre and the lessons of aesthetics. This idea is modified with respect to the classical age and antiquity with the emergence of the principle of subjectivity in art. In this manner, the historical, reflexive, and comprehensive aspects of art which anticipate a hermeneutics of art under the slogan “art for us” are uncovered: an art which is no longer anchored in representations of the past but stands before the demands of the present.